2015
DOI: 10.3892/etm.2015.2220
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin inhibits the proliferation of A431 cells by modulating the PI3K/Akt signaling pathway

Abstract: The ability of metformin, an antidiabetic drug with wide applications, to inhibit tumor cell growth has recently been discovered. The PI3K/Akt signaling pathway has been found to play an important role in the survival, proliferation and apoptosis of tumor cells. The aim of the present study was to explore the effect of metformin on the proliferation of A431 human squamous cell carcinoma cells and the underlying molecular mechanisms. A431 cells in the logarithmic growth phase were treated with 0, 15, 30, 45 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…To determine whether metformin promotes cell apoptosis, HaCaT cells were treated with the indicated concentration of metformin and then analyzed by flow cytometry following annexin V-FITC and PI dual labeling. Similar to previous reports, 17,18 metformin treatment also exerts a dose-dependent increase in the number of apoptotic cells ( Figure 1B and 1C). Moreover, metformin treatment induced cell cycle arrest in the G0-G1 phase in a dose-dependent manner as shown in Figure 1D.…”
Section: Metformin Inhibited Hacat Cells Proliferation and Promotedsupporting
confidence: 91%
“…To determine whether metformin promotes cell apoptosis, HaCaT cells were treated with the indicated concentration of metformin and then analyzed by flow cytometry following annexin V-FITC and PI dual labeling. Similar to previous reports, 17,18 metformin treatment also exerts a dose-dependent increase in the number of apoptotic cells ( Figure 1B and 1C). Moreover, metformin treatment induced cell cycle arrest in the G0-G1 phase in a dose-dependent manner as shown in Figure 1D.…”
Section: Metformin Inhibited Hacat Cells Proliferation and Promotedsupporting
confidence: 91%
“…It has been recognized that it also has antitumor properties. Metformin leads to activation of AMPK, which is a mechanism of action similar to RPA . Accordingly, several studies suggested that metformin enhances the oncologic action of sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin leads to activation of AMPK, which is a mechanism of action similar to RPA. (43)(44)(45) Accordingly, several studies suggested that metformin enhances the oncologic action of sorafenib. Metformin in combination with sorafenib prevented HCC recurrence in mice after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report has indicated that metformin may improve treatment resistance in hypoxic cell lines (27). Metformin is widely used worldwide as a therapeutic agent for type 2 diabetes, but also has antitumor effects in some types of cancer cell lines, including cholangiocarcinoma, ovarian cancer, pancreatic cancer, and epidermoid carcinoma (28)(29)(30)(31). Metformin exhibits its antitumor effects via inhibition of mTOR by activation of AMPK (32).…”
Section: Discussionmentioning
confidence: 99%